Analisis Biaya Satuan Pendidikan Pada Pondok Pesantren Al-Islam Yogyakarta - Darussalam, Haris; Hafni, Diska Arliena (AKTSAR: Jurnal Akuntansi Syariah, 2022)
This study aims to determine the cost of education units using the Activity Based Costing method at the Al-Islam Islamic Boarding School in Yogyakarta. This research was descriptive research with a quantitative approach. Interviews, documentation, and observation were used to collect research data. The data were analyzed using a comparative descriptive analysis method. The study’s results showed that the determination of unit costs using the ABC system was higher than the cost of education set by Islamic boarding schools. These results indicate an under-cost position. Under-cost means that the actual cost is lower than the cost according to the calculation of Activity Based Costing because several costs are not detailed/identified and not charged to the students by the Islamic Boarding School.